Association Between Lipid Accumulation Product and Target Organ Damage in Elderly Population: The Northern Shanghai Study - Zhao S (Dove Medical Press, 2021)
Song Zhao, Zhongyuan Ren, Shikai Yu, Chen Chi, Jiamin Tang, Rusitanmujiang Maimaitiaili, Jiadela Teliewubai, Jiaxin Li, Yawei Xu, Yi Zhang Department of Cardiology, Shanghai Tenth People’s Hospital, School of Medicine, Tongji University, Shanghai, 200072, People’s Republic of ChinaCorrespondence: Yi Zhang; Yawei XuDepartment of Cardiology, Shanghai Tenth People’s Hospital, School of Medicine, Tongji University, 301 Yanchang Road, Shanghai, 200072, People’s Republic of ChinaTel/ Fax +86 18917686332Email yizshcn@gmail.com; xuyawei@tongji.edu.cnIntroduction: Lipid accumulation product (LAP), calculated from waist circumference (WC) and triglycerides (TG), is a novel index that correlates cardiovascular disease. We aimed to investigate the relationship between LAP and target organ damage (TOD) in elderly Chinese community-dwelling individuals.Materials and Methods: We enrolled 3363 participants whose age was ≥ 65 years old. TOD, including left ventricular hypertrophy (LVH), arterial stiffness (AS), lower extremity atherosclerotic (LEA), micro-albuminuria (MAU) and chronic kidney disease (CKD), was measured using standard methods. LAP was calculated as (WC– 65) × TG in men and (WC– 58) × TG in women. Both quartiles and continuation of LAP were analyzed.Results: Age-sex adjusted partial correlation analysis showed that LAP was significantly associated with CVD risk factors. With the first quartile (Q1) as a reference, in univariate logistic regression, the fourth quartile (Q4) of LAP was associated with all TOD. In multivariate model, Q4 of LAP was only associated with an increased risk of AS (odds ratio (OR) = 1.88, 95% confidence interval (CI): 1.37– 2.58, Pfor trend< 0.001), MAU (OR = 1.33, 95% CI: 1.01– 1.75, Pfor trend= 0.02) and CKD (OR = 2.39, 95% CI: 1.39– 4.12, Pfor trend< 0.001). But, Q4 of LAP was not associated with an increased risk of LVH (OR = 1.19, 95% CI: 0.85– 1.65, Pfor trend= 0.25) or LEA (OR = 0.87, 95% CI: 0.58– 1.29, Pfor trend= 0.96). Similar associations were found when analyzed continuously.Conclusion: The novel metabolic parameter LAP is significantly and independently associated with an increased risk of arterial stiffness, chronic kidney disease and micro-albuminuria in Chinese community-dwelling elderly individuals.Keywords: lipid accumulation product, target organ damage, elderly